2018
DOI: 10.1111/jocd.12768
|View full text |Cite
|
Sign up to set email alerts
|

Two‐phase delivery using a horse oil and adenosine‐loaded dissolving microneedle patch for skin barrier restoration, moisturization, and wrinkle improvement

Abstract: HOS-Ad-DMN patches are a safe and efficient system for skin restoration and wrinkle improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…In 498 study subjects (87%) the treatment location was on the face, in 46 study subjects (8%) on the extremities and in 27 study subjects (5%) the location was in an easily accessible place for the study person (the chest, arms and shoulder). The preponderance of female patients and face as a region of interest is due to the considerable amount of included studies on facial wrinkle improvement 19–25,27,28,30,32 . In 15 articles, 16,19–28,30–33 hyaluronic acid was utilized as a polymer basis for the DMN.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 498 study subjects (87%) the treatment location was on the face, in 46 study subjects (8%) on the extremities and in 27 study subjects (5%) the location was in an easily accessible place for the study person (the chest, arms and shoulder). The preponderance of female patients and face as a region of interest is due to the considerable amount of included studies on facial wrinkle improvement 19–25,27,28,30,32 . In 15 articles, 16,19–28,30–33 hyaluronic acid was utilized as a polymer basis for the DMN.…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al 32 compared DMN loaded with horse oil and Ad to Ad‐loaded DMN (HOS‐Ad‐DMN & Ad‐DMN, respectively). The research group found an improvement in skin elasticity, skin hydration, average and maximum depth of wrinkles in both groups after 8 weeks of treatment compared to baseline.…”
Section: Resultsmentioning
confidence: 99%
“…Results obtained showed that Ado was delivered via the horse DMNs (HOS‐Ado‐DMN) after skin penetration and horse oil was delivered into the skin through the microchannels created by the Ado‐DMNs. This formulation was compared with Ado‐DMN patches and results revealed that there is significantly improved skin elasticity, hydration, dermal density, and wrinkles with HOS‐Ado‐DMN without adverse effects 66 …”
Section: Ado Formulationsmentioning
confidence: 99%
“…This formulation was compared with Ado‐DMN patches and results revealed that there is significantly improved skin elasticity, hydration, dermal density, and wrinkles with HOS‐Ado‐DMN without adverse effects. 66 …”
Section: Ado Formulationsmentioning
confidence: 99%
“…Combined approaches have led to improved transdermal delivery and efficacy compared to the individual applications of DMN or topical formulations. Another study reported the use of a two-phase (hydrophilic and lipophilic phase) delivery system consisting of a DMN patch (containing adenosine) and horse oil spread on the edge of the patch [15]. The oil phase was delivered into the skin through the channels created by the DMNs, and adenosine, a hydrophilic drug loaded within the DMNs, was delivered.…”
Section: Introductionmentioning
confidence: 99%